Sagot :
1. 2x² + 3x - 7 = 0
Solution:
3x - 2x² = 7
3x - 2x² - 7 = 0
2x² + 3x - 7 = 0
2. 2x² - 6x + 5 = 0
Solution:
5 - 2x² = 6x
5 - 2x² - 6x = 0
2x² - 6x + 5 = 0
3. x² + 3x - 7 = 0
Solution:
(x + 7)(x - 7) = -3x
x² + 3x - 7 = 0
4. x² - 8x + 8 = 0
Solution:
(x - 4)² + 8 = 0
x² - 8x + 8 = 0
#CarryOnLearning
✏️QUADRATIC
==============================
» How did you write each quadratic equation in standard form?
"We can write the quadratic equation equation in a standard form of ax² + bx + c = 0"
Quadratic Equations:
#1: 3x - 2x² = 7
- [tex] \text-2x^2 + 3x - 7 = 0 [/tex]
- [tex] \underline{\boxed{\tt \purple{2x^2 - 3x + 7 = 0}}} [/tex]
[tex] \: [/tex]
#2: 5 - 2x² = 6x
- [tex] \text-2x^2 - 6x + 5 = 0 [/tex]
- [tex] \underline{\boxed{\tt \purple{2x^2 + 6x - 5 = 0}}} [/tex]
[tex] \: [/tex]
#3: (x + 7)(x - 7) = -3x
- [tex] x^2 - 49 = \text-3x [/tex]
- [tex] \underline{\boxed{\tt \purple{x^2 + 3x - 49 = 0}}} [/tex]
[tex] \: [/tex]
#4: (x - 4)² + 8 = 0
- [tex] x^2 - 8x + 16 + 8 = 0 [/tex]
- [tex] \underline{\boxed{\tt \purple{x^2 - 8x + 24 = 0}}} [/tex]
==============================
#CarryOnLearning
(ノ^_^)ノ